ChemInform Abstract: Visible‐Light Photoredox‐Catalyzed Synthesis of Nitrones: Unexpected Rate Acceleration by Water in the Synthesis of Isoxazolidines. Issue 48 (2nd December 2014) - Hou, Hong; Zhu, Shaoqun; Pan, Fangfang; Rueping, Magnus
Abstract For the first time, a visible‐light mediated oxidative nitrone formation / [3 + 2] cycloaddition reaction is used for the synthesis of isoxazolidines.